“Nivel de conocimiento sobre estimulación prenatal en gestantes atendidas en el hospital II-1 Moyobamba Julio – Diciembre 2011” - Hinostroza Matos, Rocío Del Pilar (2011)
This research entitled knowledge about prenatal stimulation with pregnant women treated at the Hospital 11-1 Moyobamba during the period July-December 2011, understanding the great need to help expectant mothers with this piece of Peru called Moyobamba in which for lack of knowledge, the fetus is poorly stimulated. The goals we set were to determine knowledge about prenatal stímulation, to determine the socio-demographic characteristics, determine the knowledge about the concept, start time, benefrts and professional in charge of prenatal stimulation, to determine the technical knowledge of touch, visual , auditory and motor stímulation in pregnant women attending prenatal Hospital 11-1 Moyobamba during the period July to December 2011. We performed a basic study, quantitative, descriptiva, cross-sectional, with prospective collection of data, probability sampling, 133 pregnant women. We used a structured interview format, the same that consisted of 03 sections, sociodemographic characteristics of pregnant women, knowledge about the concept, the time, the benefit and in charge of prenatal stimulation 1, and knowledge about prenatal stimulation techniques. For processing and data analysis used descriptiva statistics such as frequency, percentage, arithmetic mean, in a database in Ex:cel 2.011. With the results are arrived at the following conclusions: that the level of knowledge that pregnant women are treated in Hospital 11-1 Moyobamba on prenatal stimulation is low, whereas, 75.94% belong to the age group over mujeress 20, 66.92% of pregnant women are marital status married, 56.93% of pregnant women have secondary vii education and 90.23% live in urban areas, the 77.44% did not know the concept of prenatal stimulation, 40% know the initiation of prenatal stimulation, the 72.18% did not know the benefrts of prenatal stimulation and 51.88% responded that the obstetrician is the professional who must perform prenatal stimulation, the low level of 72.18 have the technical knowledge of touch, the 76.69% have little knowledge about the visual, 57.19% regular technical knowledge about hearing and 98.50% under the level of technical knowledge about the motor. We intended to do to get the importance and necessity of our study, so that the Hospital implement and bid prenatal stimulation program, considering their great contribution to the mother-child and in turn raise the awareness of Obstetricians on the subject, to strengthen academic activities in college. Keywords: knowledge, skills, prenatal stimulation.